Review: Homo, Hunter-gatherer, Habermas: An Inquiry into Deliberation and Human Nature (PhD by Ramon van der Does Université catholique de Louvain) - van Leeuwen, Florian (Politics of the Low Countries, 2025)
The dissertation asks a simple but important question – why do people deliberate? The dissertation is well-written and includes both a thorough theoretical analysis and different empirical methods, which demonstrates ambition and innovation. It does not give a definitive answer to the main question, but maybe that is just because simple questions do not imply easy answers.